TOBACCO ASSOCIATED ORAL LESIONS AND LEVELS OF DEPENDENCE AMONG ADULT MALE PATIENTS VISITING A DENTAL HOSPITAL IN CHENNAI - Deb Barma, Manali; Kumar.R, Pradeep; Prabakar, Jayashri (International Journal of Psychosocial Rehabilitation, 2020)
Background and aim: Smoke and smokeless tobacco use cause extreme effects on soft and hard tissues in and around the oral cavity. A routine intraoral examination by a dental health professional can reveal most of these lesions at an early stage and prevent serious sequelae. The aim of the study was to assess the tobacco-associated oral lesions and level of dependence among male patients attending a private dental college in Chennai. Materials and method: The study was conducted in a hospital setting by retrieving data from the case records of 483 patients from the time period between August 2019 and January 2020. Descriptive statistics and Chi-square tests were used. Results: The study population consisted of male tobacco smokers.The participants were categorised based on index age groups. The habit of smoking tobacco was found in 65.9%, and smokeless tobacco was found to be in usage among 34.1% of the population. Leukoplakia (14.3%) was the most common lesion that was observed in the study population after tobacco stains (52.4%), followed by oral submucous fibrosis (10.6%) Statistically significance observed between tobacco induced oral lesion and tobacco dependence (p <0.05). The comparison between form of tobacco usage and nicotine dependence level was also found to be statistically significant (p <0.05). Conclusion: The higher the dependence on tobacco, the greater the risk of the development of oral mucosal lesions, suggesting a dose-response relationship.